A model for integrated tourism infrastructure planning in the South African public sector - Chettiar, Shamilla (My University, 2024)
Infrastructure supports competitiveness, productivity and economic growth. While planning is critical for co-ordination and delivery of infrastructure, integrated infrastructure planning models remain elusive. Integrated infrastructure planning is especially important to derive maximum benefits from limited public sector funding. This research focussed on infrastructure planning in the tourism context. Within the complex South African public sector planning system, the responsibility for infrastructure and tourism planning lies with multiple departments at national, provincial and local government spheres. Tourism infrastructure needs can therefore best be addressed through integrated planning. This thesis presents the results of a qualitative, multi-method study. Various methods, such as reviews of documents, key-informant interviews, focus groups and case studies were utilised to gather data. The research also contains the reflections of the researcher who has extensive experience in public sector planning. The research question was: “What are the key elements of a model for integrated tourism infrastructure planning undertaken by the South African public sector?” The model proposes three key elements - a National Tourism Spatial Development Framework; Regional Tourism Masterplans; and a Tourism Infrastructure Strategy and Plan. A People component has also emerged as being significant for the effectiveness of the model. The study further confirmed that the model will support the integration of tourism, economic, spatial and infrastructure planning and development. In the long - term integrated public sector tourism infrastructure planning in South Africa, should yield greater public sector investment, stimulate greater private sector investment, and ultimately support the growth and competitiveness of the tourism sector. This research makes a significant contribution to knowledge for integrated infrastructure planning.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2023
Keywords: Integrated infrastructure; Tourism infrastructure planning